Crafting a vision & mission statement for the competition commission of India - Sharma, Sunil, 1960- (SAGE Knowledge. Cases., 2014)
The case describes the process of formulating Vision and Mission (hereafter V&M) statement for a competition regulator. It provides chronology of setting up the commission and also describes the focus of the act, some recent penalties imposed on firms, and the need to formulate the V&M statement. The process included the identification of stakeholders, methodology for seeking their views, and brief descriptions of the views expressed by the stakeholders. Participants are challenged to develop a V&M statement for the commission.